2019
DOI: 10.1016/j.jcot.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Insertion anatomy of the pectoralis major tendon

Abstract: Tip of the greater tuberosity to pectoralis major distance Pectoralis major tendon tear Pectoralis major tendon repair a b s t r a c t Background: Pectoralis major tendon tears are encountered in young active patients. Methods: In 10 fresh cadaveric shoulders we measured-1. Proximal to distal insertion width of the pectoralis major tendon. 2. The distance of the superior border of the tendon from the supero-medial tip of the greater tuberosity (GT). Results: The average insertion width was 46 mm. The average d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The innervation to the PM is via the medial and lateral pectoral nerves, which arise from the medial and lateral cords of the brachial plexus, respectively 96,98 . Beheiry studied the innervation to the PM in 30 cadaveric thoraxes and found that the lateral pectoral nerve contributed the majority of the innervation 98 .…”
Section: Pm Muscle Anatomy and Tear Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The innervation to the PM is via the medial and lateral pectoral nerves, which arise from the medial and lateral cords of the brachial plexus, respectively 96,98 . Beheiry studied the innervation to the PM in 30 cadaveric thoraxes and found that the lateral pectoral nerve contributed the majority of the innervation 98 .…”
Section: Pm Muscle Anatomy and Tear Characteristicsmentioning
confidence: 99%
“…The tendon length is longer on the posterior surface compared with the anterior surface. The 2 tendons are usually contiguous inferiorly but can be separated superiorly and more medially, and they unite to form a common tendon that inserts onto the lateral lip of the intertubercular groove 10,[90][91][92][93][94][95][96] . Only a small number of cadaveric studies have reported PM tendon dimensions, which are found to be highly variable 93,96,97 .…”
Section: Pm Muscle Anatomy and Tear Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 18 , 19 These heads converge into a tendon distal to the axilla, inserting on the lateral lip of the bicipital groove. 20 , 21 , 22 The PM has a large insertional footprint, which is typically 63 to 68 mm in length from proximal to distal. 20 For National Football League (NFL) athletes, the PM is essential to ensure full athletic potential, functioning as a powerful adductor, internal rotator, and flexor of the humerus, providing strength and range of motion to meet the competition demands of multiple positions.…”
mentioning
confidence: 99%